Transforming mobility governance: challenges faced in Germany - Alexander Rammert (Discover Sustainability)
Abstract This paper explores the structural challenges within German mobility governance, highlighting how traditional administrative frameworks impede effective and integrated mobility planning. Current hierarchies and rigid task specialization are shown to create barriers to the interdisciplinary collaboration required for addressing modern mobility needs, such as socio-environmental sustainability and responsive public service. Traditional practices and compartmentalized departmental roles restrict flexibility and collaboration, hindering efforts to align with broader European mobility goals. Through various case studies, the article demonstrates how forward-thinking planners circumvent these structural limitations by adopting adaptive, cross-functional strategies, although often at personal cost and with significant overtime. To enable more responsive governance, the paper suggests transitioning to decentralized, agile administrative models that feature flat hierarchies and flexible team structures. This approach emphasizes integrated planning that considers human-centered and ecological aspects, encouraging a more cohesive and sustainable framework. Last the paper shows the importance of political support and a reformed legal framework to empower administrations to innovate and implement comprehensive, people-focused mobility solutions. Ultimately, it calls for structural reforms and a cultural shift within public administration to overcome systemic inertia and build a governance structure equipped to meet the complex demands of sustainable mobility in Germany.